Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.jafc.2c00672
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin Derivatives Containing Sulfonamide and Dithioacetal Moieties: Design, Synthesis, Antiviral Activity, and Mechanism

Abstract: Cucumber mosaic virus (CMV) is currently a known plant virus with the most hosts, broadest distribution, and economic hazard. To develop new antiviral drugs against this serious virus, a new range of coumarin derivatives containing sulfonamide and dithioacetal structures were designed and synthesized, and their anti-CMV activities were detected by the half-leaf dead spot method. The results of the biological activity assay showed that most of the compounds exhibited outstanding anti-CMV activity. Especially, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 45 publications
(78 reference statements)
1
8
0
Order By: Relevance
“…Previous studies have revealed that aliphatic derivatives do not possess the same anti‐CMV viral activity as aromatic and heterocyclic rings, and aliphatic derivatives showed poor anti‐CMV activity 22 . We also found that the anti‐CMV activities were higher when R was benzene ring derivatives.…”
Section: Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…Previous studies have revealed that aliphatic derivatives do not possess the same anti‐CMV viral activity as aromatic and heterocyclic rings, and aliphatic derivatives showed poor anti‐CMV activity 22 . We also found that the anti‐CMV activities were higher when R was benzene ring derivatives.…”
Section: Resultssupporting
confidence: 45%
“…Previous studies have revealed that aliphatic derivatives do not possess the same anti-CMV viral activity as aromatic and heterocyclic rings, and aliphatic derivatives showed poor anti-CMV activity. 22 We also found that the anti-CMV activities were higher when R was benzene ring derivatives. Furthermore, benzene ring derivatives without substituent are not as effective as those containing substituent, particularly those with electron-absorbing groups, which have been found to have the best anti-CMV activity.…”
Section: Structure-activity Relationship Analysismentioning
confidence: 59%
“…Imidazo­[1,2- c ]­pyrimidin-5­(6 H )-one has a wide range of antiviral activities such as hepatitis B virus (HBV) and cytomegalovirus (CMV). , Other studies had shown that 2-, 3-, 6-, 7-, and 8-substituted imidazo­[1,2- c ]­pyrimidin-5­(6 H )-one could inhibit cyclin-dependent kinase 2 (CDK2); structure–activity relationships indicated that the smaller the 8-position substituent, the higher the activity, while the larger the substituent, the lower the activity. Further studies revealed that nucleosides with imidazo­[1,2- c ]­pyrimidin-5­(6 H )-one exhibited good activities against HBV and human immunodeficiency virus (HIV). ,, The sulfonamide scaffold plays an important role in the development of antibacterial, insecticidal, , herbicidal, and antiviral, and it can be considered as “molecular chimera”, which is found to form hydrogen bonds as well as interact with unipolar environments within proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Coumarins, potential alternatives for chemical insecticides, are widely distributed in Compositae, Apiaceae, and Leguminosae, among others. , Even more intriguing, it displayed broad-spectrum bioactivities, including antiviral, antibacterial, anticancer, and especially potent insecticidal effects. Conversely, some coumarin analogues naturally, such as scoparone and scopoletin, displayed no toxicity toward the pollinators.…”
Section: Introductionmentioning
confidence: 99%